Pendekatan Hermeneutika Kontekstual Dalam Tafsir Al-Qur’an: Kajian Kritis Terhadap Metodologi Fazlur Rahman Dan Abdullah Saeed - Tomi Satria; Duski Samad; Firdaus ST Mamad (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
The development of modern Qur’anic studies presents methodological challenges to the authority and interpretation of the Qur’an, thus requiring a scientific approach capable of integrating historical dimensions with contemporary contexts in a balanced manner. This research aims to analyze the concept of hermeneutics within Qur’anic studies and to examine its applicability through a contextual approach while maintaining the principles of Islamic epistemology. The study employs a library research method with a descriptive-analytical qualitative approach, involving a comparative analysis of the ideas of leading Qur’anic hermeneutic scholars such as Fazlur Rahman and Abdullah Saeed through primary and secondary sources. The findings indicate that hermeneutics can serve as a relevant interpretive tool in understanding modern social dynamics while enriching tafsir methodology without negating the authority of revelation. Its selective application—based on the objectives of Islamic law (maqāṣid al-sharī‘ah) and the boundaries of definitive rulings (qat‘i)—offers contextual, humanistic, and responsive interpretations aligned with the needs of the Muslim community. In conclusion, hermeneutics can function as an alternative approach that strengthens the relevance of the Qur’an, provided that it is grounded in a solid Islamic epistemological framework and does not contradict the fundamental principles of Islamic teachings